PERBANDINGAN METODE SES DAN METODE DES UNTUK PERAMALAN PENJUALAN ALAT PANCING PADA TOKO PANCING GT - Ocha Fatanjali Yuharsyah; Devita Maulina Putri (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2024)
Toko Pancing GT, is an UMKM that specialize in the sale of fishing equipment. This research is used forecasting on fishing equipment sales, because since February 2024 Toko Pancing GT has experienced sales fluctuations, which has caused a lot of out-of-stock items and made inventory planning less optimal. The method used to solve this problem using Single Exponentional Smoothing and Double Exponentional Smoothing methods, for the Single Exponentional Smoothing Method, the smallest forecasting results were found using alpha 0,2 with MAE results of 21,1 then MSE is 872 and MAPE is 10%. For the Double Exponentional Smoothing Method, the smallest forecasting results were found by using alpha 0,034 and beta 1 with MAE results of 17,916 then MSE is 849,826 and MAPE is 9%. The most effective method for forecasting fishing equipment sales is the Double Exponentional Smoothing Method, because the MAPE in the Double Exponentional Smoothing method is below 10%, it means that the Double Exponentional Smoothing method is considered very good in doing this forecasting.